The chromosomal proteins JIL-1 and Z4/Putzig regulate the telomeric chromatin in Drosophila melanogaster. - Rute Silva-Sousa; Elisenda López-Panadès; David Piñeyro; Elena Casacuberta (PLoS Genetics)
Drosophila telomere maintenance depends on the transposition of the specialized retrotransposons HeT-A, TART, and TAHRE. Controlling the activation and silencing of these elements is crucial for a precise telomere function without compromising genomic integrity. Here we describe two chromosomal proteins, JIL-1 and Z4 (also known as Putzig), which are necessary for establishing a fine-tuned regulation of the transcription of the major component of Drosophila telomeres, the HeT-A retrotransposon, thus guaranteeing genome stability. We found that mutant alleles of JIL-1 have decreased HeT-A transcription, putting forward this kinase as the first positive regulator of telomere transcription in Drosophila described to date. We describe how the decrease in HeT-A transcription in JIL-1 alleles correlates with an increase in silencing chromatin marks such as H3K9me3 and HP1a at the HeT-A promoter. Moreover, we have detected that Z4 mutant alleles show moderate telomere instability, suggesting an important role of the JIL-1-Z4 complex in establishing and maintaining an appropriate chromatin environment at Drosophila telomeres. Interestingly, we have detected a biochemical interaction between Z4 and the HeT-A Gag protein, which could explain how the Z4-JIL-1 complex is targeted to the telomeres. Accordingly, we demonstrate that a phenotype of telomere instability similar to that observed for Z4 mutant alleles is found when the gene that encodes the HeT-A Gag protein is knocked down. We propose a model to explain the observed transcriptional and stability changes in relation to other heterochromatin components characteristic of Drosophila telomeres, such as HP1a.